UJI DAYA TERIMA DAN KANDUNGAN ZAT GIZI DODOL DENGAN PENAMBAHAN TERUNG UNGU (Solanum melongena) DAN KULIT BUAH PEPAYA (Carica papaya L) - Agnes Olivia Tampubolon; Albiner Siagian; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Dodol is classified into classes, prepared from fruits and prepared from flour such as rice flour and glutinous flour. During the time, the usage of eggplants on society just for vegetable, dishes and less of interest. There is various way to produce it becomes dodol. In general, society just threw up the papaya peel. Its underutilized even the nutrient content usefull for health. The purpose of this research is to know the acceptability and nutrient content of dodol with purple eggplant and papaya peel addition. The research conducted with experimental research using complete random design with to treatment. The addition of purple eggplant andpapaya peel with comparison 70%:30% (treatment A1) and comparison of 50%:50% (treatment A2). The hedonic test of dodol with purple eggplant and papaya peel addition made against 30 students of the Faculty of Public Health University of Sumatera Utara. The analysis of nutrient content held on research and Industry Standardization Laboratory Medan and Technology Laboratory Faculty of Agriculture University of Sumatera Utara. Organoleptic data analysed with Wilcoxon Signed-Ranks Test. The result of nutrient content analysis in dodol with purple eggplant and papaya peel addition on treatment A1 (70%:30%) contain carbohydrates 23,4%, fiber 1,23%, posfor 65,2 mg/100g and contain beta carotene 0,34 mg/100g. The result of nutrient content analysis for treatment A2 (50%:50%) contain carbohydrates 23,4%, fiber 1,02%, posfor 84,3 mg/100g and contain beta carotene 0,20 mg/100g. Based on organoleptic test on color, smell, taste, and texture its found that panelis preferred dodol with comparison (70%:30%). It is suggested for society to utilize purple eggplants and papaya peel in producing another kinds of dodo and can be used as a small business cental that increasing income and increasing the diversity of dodol processed products from vegetable ingredients and papaya peel. Keywords: Dodol, Eggplant, Papaya peel, Nutrient content, Hedonic test